Constraining the parameter space of a quantum spin liquid candidate in applied field with iterative optimization - William Steinhardt; Zhenzhong Shi; Anjana Samarakoon; Sachith Dissanayake; David Graf; Yaohua Liu; Wei Zhu; Casey Marjerrison; Cristian D. Batista; Sara Haravifard (Physical Review Research, 2021)
The quantum spin liquid (QSL) state is an exotic state of matter featuring a high degree of entanglement and lack of long-range magnetic order in the zero-temperature limit. The triangular antiferromagnet YbMgGaO_{4} is a candidate QSL host, and precise determination of the Hamiltonian parameters is critical to understanding the nature of the possible ground states. However, the presence of chemical disorder has made directly measuring these parameters challenging. Here we report neutron scattering and magnetic susceptibility measurements covering a broad range of applied magnetic field at low temperature. Our data shows a field-induced crossover in YbMgGaO_{4}, which we reproduce with complementary classical Monte Carlo and density matrix renormalization group simulations. Neutron scattering data above and below the crossover reveal a shift in scattering intensity from M to K points and, collectively, our measurements provide essential characteristics of the phase crossover that we employ to strictly constrain proposed magnetic Hamiltonian parameters despite the chemical disorder. Constrained exchange parameters further suggest the material's proximity to the QSL state in the clean limit. More broadly, our approach demonstrates a means of pursuing QSL candidates where Hamiltonian parameters might otherwise be obscured by disorder.